Analysis of glass eel fishing in 1996 using the data recorded on fishing book - Castelnaud, Gérard; Carpentier, Alexandra (HAL CCSD, 1996)
The professional fishing of glass eel with pushing nets has been authorized in the lower part of the Garonne, Dordogne and Isle river during the 1996 season. This report analyse the data recorded on fishing book by the professionnal fishermen in order to set up a first evaluation. La pêche professionnelle de la civelle par la technique du drossage a été autorisée du 1er janvier au 15 avril 1996 sur l'ancienne zone mixte de Garonne-Dordogne-Isle sous conditions, notamment la tenue d'un carnet de pêche. Le Cemagref a été chargé d'analyser les données recueillies. Il s'agit de faire un bilan de la pêche de la civelle d'anguille Anguilla anguilla par drossage.